2009
DOI: 10.1007/s00432-009-0583-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer in the era of molecularly targeted agents: current drug development strategies

Abstract: Gastric cancer is the second most common cause of cancer death worldwide with approximately one million cases diagnosed annually. Despite considerable improvements in surgical techniques, innovations in clinical diagnostics and the development of new chemotherapy regimens, the clinical outcome for patients with advanced gastric cancer and cancer of the GEJ is generally poor with 5-year survival rates ranging between 5 and 15%. The understanding of cancer relevant events has resulted in new therapeutic strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 85 publications
0
40
0
Order By: Relevance
“…In particular, molecular therapies targeted against EGFR increase the impact of treatment in breast and colorectal cancer patients (26,27). Recently, it was shown that therapy targeted against EGFR had a beneficial effect on gastric cancer patients in clinical trials (28,29). IRAK1 and subsequent NF-kB activation is associated with poor prognosis and invasion in gastric cancer (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, molecular therapies targeted against EGFR increase the impact of treatment in breast and colorectal cancer patients (26,27). Recently, it was shown that therapy targeted against EGFR had a beneficial effect on gastric cancer patients in clinical trials (28,29). IRAK1 and subsequent NF-kB activation is associated with poor prognosis and invasion in gastric cancer (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that receptor tyrosine kinases such as the vascular growth factor receptor (VEGFR; Mannell et al, 2012) epidermal growth factor receptor (EGFR) and insulin/insulin-like growth factor receptors (InR/ IGF-Rs) play prominent roles in signaling cell proliferation and differentiation (reviewed by Schlessinger, 2004). Misregulation of both pathways is often causative for tumor development and progression through their effects on uncontrolled cell growth, inhibition of apoptosis, angiogenesis, and tumor-associated inflammation (Witte et al, 2009;Alvarez et al, 2010;Antonarakis et al, 2010;Arkenau, 2009). Determining how growth and differentiation are coordinated by these pathways is thus essential to understanding normal development, as well as disease states such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and pathological studies have shown that gastric cancer is a complex, multistep and multifactorial process, involving numerous genetic and epigenetic alterations, such as abnormalities in growth factors/receptors, angiogenic factors, cell cycle regulators and DNA mismatch repair (MMR) genes. These abnormalities also define biological characteristics of gastric cancer cells, which are capable of serving as therapeutic targets for gastric cancer (5).…”
Section: Introductionmentioning
confidence: 99%